Geochemical characteristics of the No. 10 Coal Seam, Chazhuang Mine, Luxi Region, China: Emphasis on the mechanisms of REY enrichment - Xue Zheng; Daiting Han; Mengjing Zhou; Wentao Chen; Munira Raji; Dongdong Wang; Meng Zhang; Taitao Liang; Dawei Lv (Journal of Geochemical Exploration, 2026)

Deciphering the degradation pathway and acclimation-driven adaptive evolution characteristics of a novel sulfamethoxazole-degrading strain Bacillus cereus SDB-X - Qingru Chen; Ying Liu; Xiaohui Liu; Qingzhe Xu; Zheng Sun; Caili Zhang; Yongxin Li; Bin Zhao; Dawei Gao; Yan Zhang; Binbin Huang; Shenghai Huang; et al. (Chemical Engineering Journal, 2026)

Impact of emerging contaminants on phosphorus recovery in batch and fluidized-bed reactors: Kinetic and mechanistic insights - Xianfei Wang; Degui Gao; Mengyu Ma; Ruxin Han; Bing Li; Dawei Li; Feihu Li (Bioresource Technology, 2026)

A Neuroimaging Biomarker for Hippocampal Network Dysfunction in Alzheimer’s Disease - Jiangping Wu; Pan Wang; Dawei Wang; Hongxiang Yao; Bo Zhou; Jie Lu; Xi Zhang; Ying Han; Yonghua Zhao; Yihe Zhang; Kun Zhao; Yong Liu (Neuroscience Bulletin, 2026)

Microbial additive and biochar co-application enhances biotransformation of kelp waste into nitrogen-retentive, humified biofertilizer with high agronomic efficiency - Min Xie; Dawei Feng; Derui Wang; Yiran Han (Biocatalysis and Agricultural Biotechnology, 2026)

Optimal design and performance evaluation of outrigger systems augmented with tuned viscous mass dampers - Dawei Li; Jianting Wang; Kangqian Xu; Jianping Han; Yonggang Gao (Bulletin of Earthquake Engineering, 2026)

Channel ratio normalized calibration of the solar reflectance bands from FY-3D/MERSI lunar observations - Kang Chen; Zhongyi Han; Zhao Wang; Yujie Cui; Mingkun Wang; Hanbo Zhen; Peng Gao; Jingjing Ai; Chengli Qi; Dawei Zhang; Xiaolin Wang (International Journal of Remote Sensing, 2026)

Compressive and tensile failure characteristics of a variable-stiffness composite riser considering viscoelastic curing-induced residual stress - Ni Zhuang; Chao Kang; Pan Zhao; Zan Liu; Dawei Han; Jian Zhang (Ocean Engineering, 2026)

On-board determination and ecological risk of Cu species in Yellow River Estuary - Zhiwei Zhang; Haitao Han; Yuxi Lu; Xiangpeng Meng; Ning Wang; Dawei Pan (Marine Environmental Research, 2026)

Unified prediction equation for equilibrium scour depth around vibrating monopile foundations - Zishun Yao; Han Wang; Bruce Melville; B. Mutlu Sumer; Dawei Guan (Coastal Engineering, 2026)

Slip Behaviors of Granite Fault Under Stress Perturbation: An Experimental Study - Zhanguo Xiu; Fanzhen Meng; Xiong Zhou; Zhufeng Yue; Feili Wang; Muzi Li; Jianhua Han; Dawei Hu (Pure and Applied Geophysics, 2026)

The Effects of Nitrogen, Phosphorus, and Potassium Application on the Growth, Nutritional Characteristics and Active Ingredients of Astragalus membranaceus var. mongholicus - Dawei Wang; Han Luo; Weiling Wang (Journal of Soil Science and Plant Nutrition, 2026)

A denoising diffusion probabilistic model-based method for rough discrete fracture network fine modeling considering location optimization and multivariate distribution of parameters - Shuyang Han; Jiajun Wang; Dawei Tong; Xiaoling Wang; Wanyu Zhang; Jinkun Du (Computational Geosciences, 2026)

Coordination-encoded natural strong metal–support interaction for stabilizing Cu single-atom catalysts in lithium–sulfur batteries - Zhaoyang Han; Xiaotong Niu; Xinwei Guan; Tianci Ma; Minglei Jia; Juan Lian; Yan Li; Jinwei Mao; Bing Wang; Dawei Yang; Hangqi Yang; Fengzhu Ren; et al. (Chemical Engineering Journal, 2026)

Corrigendum to “MXene-enhanced multifunctional hydrogel for ultrasensitive strain sensing and self-powered triboelectric energy harvesting” [Chem. Eng. J. 525 (2025) 170080] - Zishuo Li; Liping Zeng; Peiyao He; Di Wu; Shuaiyuan Han; Yongtao Yao; Dawei Zhang; Likun Gao; Jianing Zhao; Pengfei Huo (Chemical Engineering Journal, 2026)

Dual regulation of anode corrosion and cathode oxygen evolution in alkaline sodium-ion batteries by hydrated eutectic electrolyte engineering - Zhaoyang Han; Minglei Jia; Yifan Wang; Junli Song; Bing Wang; Juan Lian; Xiaotong Niu; Fengzhu Ren; Yuanmin Zhang; Dawei Yang; Jiasheng Tong; Hangqi Yang (Chemical Engineering Journal, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Paleocene to Eocene deformation and crustal shortening history of the Tanggula Range, Central Tibet - Wenjun Bi; Yalin Li; Zhongpeng Han; Chengshan Wang; Jiawei Zhang; Tiankun Xu; Dawei Lv; Chan Wang; Zining Ma; Haiyang He; Huan Chen (Global and Planetary Change, 2026)

Overcoming strength-ductility trade-off via a plate-entangled polymer network with tunable supramolecular interactions - Baipei Liu; Yande Liu; Chunxia Chen; Yuhang Han; Jixian Shang; Miaojun Xu; Yongqiang Ma; Yuhua Lei; Mingyan He; Bo Jiang; Zijian Wu; Dawei Jiang (Chemical Engineering Journal, 2026)

Tannic-Ca2+ complex-induced rapid fabrication of anti-freezing and adhesive hydrogels for high-performance strain sensing - Haiyan Yang; Wenbo Han; Chun Shi; Dongtian Miao; Dawei Wang; Zhengjun Shi; Jing Yang; Jingjie Shen (Chemical Engineering Journal, 2026)

Spatial and temporal variation of raindrop size distribution in Great Britain - Shan Jiang; Dawei Han; Rafael Rosolem; Merhala Thurai; Miguel A. Rico-Ramirez (Atmospheric Research, 2026)

CMOS-compatible 2D semiconductor-nitride ferroelectric based optoelectronic memristive transistors for neuromorphic sensory computing and optical decoding - Fei Xiao; Dongxin Tan; Zheng-Dong Luo; Dawei Zhang; Xuetao Gan; Zhufei Chu; Fei Xue; Yinshui Xia; Yan Liu; Yue Hao; Genquan Han (Science Bulletin, 2026)

Cleavage of Beclin 1 by metacaspase 1 activates antiviral autophagy in plants - Rujian Hu; Qinglin Pi; Meng Yang; Wen Song; Zhihao Jiang; Chenchen Zhong; Huanxi Han; Cheng-Gui Han; Yongliang Zhang; Dawei Li (Molecular Plant, 2026)

Influence of Grouting Pipe Lifting Rate on Vacuum Preloading Performance for Dredged Sludge - Zhou Changchen; Jin Fangyi; Xu Li; Li Dawei; Ni Junfeng; Yan Shuaixin; Xu Mintao; Han Song; Ge Bin; Wu Yehu; Zhang Ye (Geotechnical and Geological Engineering, 2026)

Evaluation of carrying capacity of agricultural water and soil resources and targeted regional management in Northwest China - Yun Gao; Dawei Ding; Youming Zhang; Ping Li; Kaiyang Li; Tianhao Ruan; Yang Han; Chunya Ma (Journal of Environmental Management, 2025)

Changes in source contribution to particle number concentrations during the 2022 COVID-19 Lockdown on southern edge of North China Plain - Zeyu Gao; Nan Zhang; Guotao Zhang; Dawei Niu; Wen Yang; Xinhua Wang; Shengli Wang; Bin Han; Zhipeng Bai (Journal of Environmental Sciences, 2025)

MXene-enhanced multifunctional hydrogel for ultrasensitive strain sensing and self-powered triboelectric energy harvesting - Zishuo Li; Liping Zeng; Peiyao He; Di Wu; Shuaiyuan Han; Yongtao Yao; Dawei Zhang; Likun Gao; Jianing Zhao; Pengfei Huo (Chemical Engineering Journal, 2025)

A novel “WRF+AutoML” framework for enhanced heat estimation in urban environments - Meiling Gao; Huifang Li; Fei Chen; Mengzi Zhou; Guijun Yang; Dun Zhu; Dawei Han; Zhenhong Li (Sustainable Cities and Society, 2025)

Distribution characteristics of antibiotic resistance genes and their associations with bacterial communities in the river estuary - Jiaxin Zhu; Yangfan Du; Lejie Wang; Fayuan Wang; Dawei Liu; Zhaoxiang Han; Yan Zhang; Cuishuang Jiang; Picheng Gong (Journal of Environmental Chemical Engineering, 2025)

In situ monitoring of natural labile copper during the growth process of a marine diatom - Haitao Han; Ying Li; Yinchu Wang; Dawei Pan (Environmental Pollution, 2025)

Impacts of human activities on vegetation dynamics amid climate change: A case study of the Hanjiang River Basin (China) - Xiaofei Li; Peiyue Li; Meiling Gao; Dawei Mu; Dawei Han (Journal of Environmental Management, 2025)

Multi-level resource utilization of food-grade nanomaterials from brewing residues: Synergistic polyphenol-pullulan membranes for litchi preservation - Congyu Lin; Peiqi Lu; Peihang Li; Zhimin Zhang; Jingqiu Ma; Yunfei Hou; Xiao Han; Zhongwei Ji; Zhilei Zhou; Dawei Li; Jian Mao (Chemical Engineering Journal, 2025)

A Comparative Analysis of Subtyping Methodologies on Cross-sectional sMRI Data - Shirui Zhang; Baitong Zhang; Kun Zhao; Zhuangzhuang Li; Pan Wang; Dawei Wang; Chengyuan Song; Jie Lu; Zengqiang Zhang; Hongxiang Yao; Tong Han; Chunshui Yu; et al. (Neuroscience Bulletin, 2025)

Modification of myofibrillar protein using combined chicken breast and soybean protein isolate for improving gel properties: Protein structure and intermolecular interactions - Lishi Wang; Pei Gao; Qixing Jiang; Han Chen; Fang Yang; Peipei Yu; Dawei Yu; Wenshui Xia (Food Hydrocolloids, 2025)

Exploring suitable domain size for high-resolution urban rainfall simulation - Sichan Du; Lu Zhuo; Elizabeth J. Kendon; Dawei Han (Urban Climate, 2025)

Incidence, risk factors, and prognosis of hospitalized mechanical eye injuries in China: data from China Ocular Trauma Study (COTS) 2021–2023 - Han Han; Yongjie Chen; Gao Si; Guowei Huang; Jiayi Song; Wenfang Zhang; Danyan Liu; Jie Zhong; Xuemin Jin; Dawei Sun; Shenwen Liu; Yanming Huang; et al. (Science Bulletin, 2025)

On the connection between large-scale climate indices and rainfall variability in Iraq - Sherien Fadhel; Dawei Han (Dynamics of Atmospheres and Oceans, 2025)

An enzyme-activated fluorescent probe for proline aminopeptidase and its applications in anti-infection agent discovery - Ming Zhang; Lei Feng; Shengui He; Chaoyan Han; Yuzhuo Wu; Jingnan Cui; Ping Guo; Dawei Li; Chao Wang; Xiaochi Ma (Chemical Engineering Journal, 2025)

Lipid acid metabolism reprogramming nanoagent induces ferroptosis storm and cGAS-STING activation for metal-immunotherapy of triple negative breast cancer - Dawei Zhou; Gaorui Zhang; Jingze Zhu; Chen Ai; Wenbo Wang; Yuxuan Zhao; Xiaoyu Han; Yafei Qi; Jiazhi Duan; Dexin Yu (Chemical Engineering Journal, 2025)

An efficient semi-automated characterization of rock mass discontinuities from 3D point clouds based on Nutcracker Optimization Algorithm-improved probabilistic neural network - Shuyang Han; Dawei Tong; Binping Wu; Jiajun Wang; Xiaoling Wang; Wanyu Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Asymmetric non-fused-ring acceptors with thienoisochromene subunit: Synthesis and improved photoelectronic property enabled by dual-donor center skeleton enlargement and terminal chlorination - Xumeng Wang; Jiali Guo; Dawei Sun; Jieqiong Zhu; Han Wei; Hua Tan; Xin Song; Mengbing Zhu; Weiguo Zhu (Chemical Engineering Journal, 2025)

A Decade Review of Human Health Risks from Heavy Metal Contamination in Industrial Sites - Yingyue Han; Shuai Zhang; Dawei Kang; Na Hao; Jingyu Peng; Yiling Zhou; Kai Liu; Yunmin Chen (Water, Air, & Soil Pollution, 2025)

Fabrication of Ag based Surface Enhanced Raman Scattering substrates with periodic mask arrays by electron beam deposition - Tian Xing; Jiawei Wang; Jiaqing Wei; Xingxing Du; Ruijin Hong; Chunxian Tao; Qi Wang; Hui Lin; Zhaoxia Han; Dawei Zhang (Analytica Chimica Acta, 2025)

Seismic demand-oriented design of hybrid base-isolated building with the tuned inerter eddy current damper - Dawei Li; He Bai; Yu Lou; Jianping Han (Soil Dynamics and Earthquake Engineering, 2025)

Glucocorticoid efficacy and treatment strategies for drug-induced liver injury: a literature review - Punan Wang; Guanya Guo; Shuangshuang Jiang; Dawei Ding; Jiaqi Yang; Yi Lu; Ying Han; Xinmin Zhou (Molecular Biology Reports, 2024)

Improving evapotranspiration partitioning by integrating satellite vegetation parameters into a land surface model - Dawei Peng; Xianhong Xie; Shunlin Liang; Yibing Wang; Arken Tursun; Yao Liu; Kun Jia; Han Ma; Yuchao Chen (Journal of Hydrology, 2024)

Raindrop size distribution (DSD) retrieval from polarimetric radar observations using neural networks - Jingxuan Zhu; Qiang Dai; Yuanyuan Xiao; Shaonan Zhu; Lu Zhuo; Jun Zhang; Dawei Han (Atmospheric Research, 2024)

A novel fault detection and identification method for complex chemical processes based on OSCAE and CNN - Shangbo Han; Lining Yang; Dawei Duan; Longchao Yao; Kai Gao; Qingyuan Zhang; Yanwen Xiao; Weihong Wu; Jian Yang; Weijie Liu; Xiang Gao (Process Safety and Environmental Protection, 2024)

Hydrogel ionic diode with ultra-high rectification ratio for ionic circuit - Yanqing Wei; Yize Zhao; Qun Ding; Junyi Zhao; Yibing Yang; Yang Liu; Jidong Dong; Dawei Zhang; Shuaiyuan Han; Pengfei Huo (Chemical Engineering Journal, 2024)

Supersaturation- and external force-engineered high-quality 2D CsCu2I3 single-crystalline film for heterogeneous integration in photodetectors - Sancan Han; Xianyu Qiao; Yimin Li; Fei Wang; Dechao Yu; Jingcheng Xu; Songlin Zhuang; Xiaosheng Fang; Dawei Zhang (Chemical Engineering Journal, 2024)

Tiny rain makers: How aerosols shape extreme rainfall simulation accuracy - Ying Liu; Hai Liu; Lu Zhuo; Dawei Han (Journal of Hydrology, 2024)

In situ measurement of the three-dimensional distribution of labile copper in sediment pore water using a microneedle sensor with nanoporous structure - Haitao Han; Yuxuan Zhang; Jie Wang; Ruizhi Liu; Dawei Pan (Journal of Hazardous Materials, 2024)

Review of energy self-circulation systems integrating biogas utilization with Powerfuels production in global livestock industry - Gengxin Zhang; Penghua Shi; Chang Zhai; Yu Jin; Mengyao Han; Siyuan Liu; Yaowei Liu; Haoye Liu; Quan Zhou; Ji Li; Dawei Wu; Hongming Xu; et al. (Bioresource Technology, 2024)

Sources and formation of fine particles and organic aerosols during autumn-winter period in the southern edge of northern China plain - Hui Wang; Nan Zhang; Dawei Niu; Peng Wang; Xinhua Wang; Chunmei Geng; Wen Yang; Wenge Zhang; Jinbao Han; Bin Han; Zhipeng Bai (Atmospheric Environment, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

Screening and evaluation of a novel nucleotide-degrading Levilactobacillus brevis grx821 with anti-hyperuricemia ability - Haiying Wang; Jiaxing Dai; Yifeng Han; Yunchao Wa; Dawei Chen; Renqin Yang; Yujun Huang; Hua Wei; Ruixia Gu; Boxing Yin; Wenlong Ma (Food Bioscience, 2024)

In vitro susceptibility of grass carp fish (Ctenopharyngodon idella) to oxidized myosin on structural change of protein secondary structure associated with reactive oxygen species (ROS) treatment - Abuubakar Hassan Ramadhan; Dawei Yu; Qixing Jiang; Yanshun Xu; Han Chen; Lishi Wang; Wenshui Xia (Food Bioscience, 2024)

Water accumulation unrelated to ice segregation near the freezing front during soil freezing: Implications for frost heave in high-speed railway embankments and ground ice formation - Lianhai Zhang; Yajun Shi; Chengsong Yang; Wei Ma; Dawei Han; Fei Shang; Cheng Chen; Yuzhong Yang (CATENA, 2024)

Data-driven hydraulic property analysis and prediction of two-dimensional random fracture networks - Chenghao Han; Shaojie Chen; Feng Wang; Weiye Li; Dawei Yin; Jicheng Zhang; Weijie Zhang; Yuanlin Bai (Computers and Geotechnics, 2024)

Carboniferous–Early Permian volcano-sedimentary units from the northern margin of the North China Craton recorded subduction initiation in the Paleo-Asian Ocean - Qingxiang Du; Jinrui Han; Sainan Wu; Guangsu Li; Zuozhen Han; Dawei Lv; Xiaoli Shen (Lithos, 2024)

Graph neural network-based topological relationships automatic identification of geological boundaries - Shuyang Han; Yichi Zhang; Jiajun Wang; Dawei Tong; Mingming Lyu (Computers & Geosciences, 2024)

Osteocompatible Zinc-Copper Substituted Hydroxyapatite Reinforced Biocomposites for Bone Tissue Regeneration - Leixiang Han; Dawei Wang (Journal of Pharmaceutical Innovation, 2024)

A systematic review of Muskingum flood routing techniques - Aryan Salvati; Alireza Moghaddam Nia; Ali Salajegheh; Ataollah Shirzadi; Himan Shahabi; Ebrahim Ahmadisharaf; Dawei Han; John J Clague (Hydrological Sciences Journal, 2024)

Spatial and temporal patterns of above- and below- ground biomass over the Tibet Plateau grasslands and their sensitivity to climate change - Yatang Wu; Fu Li; Jing Zhang; YiLiang Liu; Han Li; Bingrong Zhou; Beibei Shen; Lulu Hou; Dawei Xu; Lei Ding; Shiyang Chen; Xiaoni Liu; et al. (Science of The Total Environment, 2024)

Assessment of natural resource endowment and urban-rural integration for sustainable development in Xinjiang, China - Keqiao Su; Dawei He; Ruixue Wang; Ze Han; Xiangzheng Deng (Journal of Cleaner Production, 2024)

A novel Ce/Fe bimetallic metal-organic framework with ortho-dodecahedral multilevel structure for enhanced phosphate adsorption - Zunchang Gao; Yanqing Wei; Xin Tian; Yang Liu; Xin Lan; Dawei Zhang; Shuaiyuan Han; Pengfei Huo (Chemical Engineering Journal, 2024)

Improve meat production and virus resistance by simultaneously editing multiple genes in livestock using Cas12iMax - Jilong Ren; Tang Hai; Yangcan Chen; Ke Sun; Zhiqiang Han; Jing Wang; Chongyang Li; Qingwei Wang; Leyun Wang; Huabing Zhu; Dawei Yu; Wei Li; et al. (Science China Life Sciences, 2024)

Field determination and ecological health risk assessment of trace metals in typical mariculture area of China - Yan Liang; Dawei Pan; Ying Li; Haitao Han; Xiaofeng Wang; Guowei Gai (Marine Pollution Bulletin, 2024)

Analysis of spatial spillover effects and influencing factors of transportation carbon emission efficiency from a provincial perspective in China - Wenyu Zhang; Xue Han; Qi Ding; Dawei Zhang (Environmental Science and Pollution Research, 2024)

Study on the suppression characteristics and mechanism of ABC powder on pulverized coal explosion based on the analysis of thermal decomposition characteristics and reaction kinetics - Bingyou Jiang; Qi Yao; Mingqing Su; Jingjing Li; Kunlun Lu; Dawei Ding; Han Hong (Process Safety and Environmental Protection, 2024)

Speciation, distribution and relationship of zinc and cadmium in summer coastal seawater of northern China - Yan Liang; Dawei Pan; Hong Wei; Haitao Han; Ying Li; Tianzhuo Liu (Marine Chemistry, 2024)

Inorganic nanoparticle-enhanced double-network hydrogel electrolytes for supercapacitor with superior low-temperature adaptability - Na Luo; Jian Wang; Dawei Zhang; Yize Zhao; Yanqing Wei; Yang Liu; Yanhua Zhang; Shuaiyuan Han; Xianzhi Kong; Pengfei Huo (Chemical Engineering Journal, 2024)

Frictional Sliding Behaviour of Rough Fracture in Granite Under True Triaxial Loading with Implications for Fault Reactivation - Fanzhen Meng; Zhufeng Yue; Muzi Li; Jianhua Han; Qijin Cai; Wei Wang; Dawei Hu; Chuanqing Zhang (Rock Mechanics and Rock Engineering, 2024)

Natural and anthropogenic factors regulating fluoride enrichment in groundwater of the Nansi Lake Basin, Northern China - Chunli Su; Mengzhu Wang; Xianjun Xie; Zhantao Han; Jiaqi Jiang; Zhen Wang; Dawei Xiao (Science of The Total Environment, 2023)

Microphysics-based rainfall energy estimation using remote sensing and reanalysis data - Jingxuan Zhu; Qiang Dai; Yuanyuan Xiao; Chaonan Liu; Jun Zhang; Lu Zhuo; Dawei Han (Journal of Hydrology, 2023)

Carbon nanotubes as a scaffold in the Ti3C2Tx(MXene)-derivatized membrane for oil/water emulsion separation - Luyuan Yang; Yitao Yang; Xin Dai; Ying Zhao; Dawei Han; Qi Zuo; Zhaozheng Song (Journal of Environmental Chemical Engineering, 2023)

Reproducible Abnormalities and Diagnostic Generalizability of White Matter in Alzheimer’s Disease - Yida Qu; Pan Wang; Hongxiang Yao; Dawei Wang; Chengyuan Song; Hongwei Yang; Zengqiang Zhang; Pindong Chen; Xiaopeng Kang; Kai Du; Lingzhong Fan; Bo Zhou; et al. (Neuroscience Bulletin, 2023)

Submarine landslides on a carbonate platform slope changing transport pathways of deepwater gravity flows: Insights from the Xisha Islands, South China Sea - Gang Liu; Dawei Wang; Wanli Chen; Weiwei Wang; Christian Betzler; Xiaohui Han (Geomorphology, 2023)

Dissected Leaf 1 encodes an MYB transcription factor that controls leaf morphology in potato - Dawei Li; Xiaoyue Lu; Duoduo Qian; Pei Wang; Dié Tang; Yang Zhong; Yi Shang; Han Guo; Zhen Wang; Guangtao Zhu; Chunzhi Zhang (Theoretical and Applied Genetics, 2023)

Dihydro-β-agarofuran sesquiterpenoids from the roots of Tripterygium regelii and their inhibitory effect on NO production - Yan Sun; Jia Liu; Jintao Sun; Honglei Wang; Shan Wu; Yuzhuo Wu; Aijing Leng; Chao Wang; Chunhui Han; Dawei Li (Phytochemistry Letters, 2023)

Developing spin-up time framework for WRF extreme precipitation simulations - Ying Liu; Lu Zhuo; Dawei Han (Journal of Hydrology, 2023)

Preparation of sludge–cyanobacteria composite carbon for synergistically enhanced co-removal of Cu(II) and Cr(VI) - Lixin Li; Ying Lv; Chao Jia; Dawei Yin; Zilong Dong; Zhaoshun Zhan; Jiazhen Han; Jun Zhang (Chemosphere, 2023)

Flavone C-glycosides from Dendrobium gratiosissimum - Zhijun Song; Jimei Liu; Changkang Li; Xincheng Sun; Dawei Chen; Ridao Chen; Kebo Xie; Yaotian Han; Jungui Dai (Phytochemistry Letters, 2023)

Silica-nickel catalyst interfaces promote highly efficient CO2 electroreduction to CO with a wide potential range - Yijun Xie; Wei Xia; Shuaiqiang Jia; Shitao Han; Ting Yao; Minghui Fang; Dawei Zhou; Xueqing Xing; Haihong Wu; Mingyuan He; Buxing Han (Chemical Engineering Journal, 2023)

Improved dynamic event-triggered anti-unwinding control for autonomous underwater vehicles - Ziyi Su; Xiaogong Lin; Bing Huang; Dawei Zhao; Han Sun (Ocean Engineering, 2023)

An antifouling gel-protected iridium needle sensor: Long-term, on-site monitoring of copper in seawater - Ying Li; Haitao Han; Chenchen Wang; Yan Liang; Dawei Pan; Haizeng Wang (Chemosphere, 2023)

Two haplotype-resolved, gap-free genome assemblies for Actinidia latifolia and Actinidia chinensis shed light on the regulatory mechanisms of vitamin C and sucrose metabolism in kiwifruit - Xue Han; Yilin Zhang; Qiong Zhang; Ni Ma; Xiaoying Liu; Wenjing Tao; Zhiying Lou; Caihong Zhong; Xing Wang Deng; Dawei Li; Hang He (Molecular Plant, 2023)

Atomically dispersed SrOx species on exposed {2 2 2} facets of pyrochlore La2Zr2O7 nanocrystals for boosting low-temperature oxidative coupling of methane - Tongtong Wu; Yuechang Wei; Jing Xiong; Yitao Yang; Dawei Han; Zhen Zhao; Jian Liu (Fuel, 2023)

Single-channel blind source separation of underwater acoustic signals using improved NMF and FastICA - Dawei Li; Minghui Wu; Liang Yu; Jianhui Han; Hao Zhang (Frontiers in Marine Science, 2023)
When automatic monitoring buoys receive mixed acoustic signals from multiple underwater acoustic targets, the statistical blind source separation (BSS) task is used to separate the signals and identify vessel features, which is overly complex and needs improvement, especially noting that noise cancellation and stealth technologies are advancing rapidly. To fill this gap in capability, an improved non-negative matrix factorization (NMF) based BSS algorithm is built on a FastICA machine learning backbone. With this tool, the spatial and spectral correlation of underwater acoustic signals is introduced into the NMF algorithm improved by to resolve the non-convex and feature correlation problems commonly encountered by contemporary NMF algorithms. Moreover, the improved modulation feature adaptability of the NMF increases the local expressivity and independence of the decomposed base matrix, which is proven to meet the requirements of FastICA and used to improve the BSS effect of the FastICA. Simulated and empirical results show that compared with state-of-the-art FastICA and NMF based BSS algorithms, our novel approach obtains better signal-to-noise reduction and separation accuracy while maintaining superior target signal recognition features.

Observer-based dynamic optimal recoil controller design for deepwater drilling riser systems - Wei Zhang; Bao-Lin Zhang; Qing-Long Han; Yue-Ting Sun; Yan Ji; Dawei Zhang; Xian-Ming Zhang (Ocean Engineering, 2023)

Changes in the m6A RNA methylome accompany the promotion of soybean root growth by rhizobia under cadmium stress - Xue Han; Jialin Wang; Yu Zhang; Youlin Kong; Huiying Dong; Xuezhen Feng; Tianshu Li; Changjun Zhou; Jidong Yu; Dawei Xin; Qingshan Chen; Zhaoming Qi (Journal of Hazardous Materials, 2023)

Environmentally friendly, non-glove box, closed-system and continuously massive production of lithium sulfide for battery applications - Shunjin Yang; Fengming Wan; Aiguo Han; Liran Fang; Qifang Sun; Zixiang Zhao; Dawei Song; Lianqi Zhang; Lifang Chen; Colin A. Wolden; Xin Zhang; Yongan Yang (Journal of Cleaner Production, 2023)

Tip-porous microneedle: A highly stable sensing platform for direct determination of labile metals in natural seawater - Haitao Han; Jie Wang; Dawei Pan; Ying Li; Chenchen Wang (Environmental Pollution, 2023)

Occupational health risk assessment of the benzene exposure industries: a comprehensive scoring method through 4 health risk assessment models - Ludi Zhang; Peng Sun; Dawei Sun; Yanhua Zhou; Lei Han; Hengdong Zhang; Baoli Zhu; Boshen Wang (Environmental Science and Pollution Research, 2022)

Lignans from Bupleurum marginatum and their antioxidant activity - Jian Zhou; Xin He; Rongjin Sun; Zhenlong Yu; Chao Wang; Sa Deng; Baojing Zhang; Shanshan Huang; Chunhui Han; Dawei Li (Natural Product Research, 2022)

Construction of a core germplasm bank of upland cotton (Gossypium hirsutum L.) based on phenotype, genotype and favorable alleles - Peng Han; Xiaomin Tian; Ying Wang; Cong Huang; Yizan Ma; Xiaofeng Zhou; Yu Yu; Dawei Zhang; Haijiang Xu; Yang Cao; Bo Zhu; Zhenxiu Feng; et al. (Genetic Resources and Crop Evolution, 2022)

Concentration, Spatial-Temporal Distribution, and Bioavailability of Dissolved Reactive Iron in Northern Coastal China Seawater - Chenchen Wang; Yongsheng Luan; Dawei Pan; Yuxi Lu; Haitao Han; Shenghui Zhang (Journal of Marine Science and Engineering, 2022)
The concentrations of total dissolved iron (TdFe) and dissolved reactive iron (DrFe) in the Northern coastal China seawater (Yantai Sishili Bay) in 2018 were determined using cathodic stripping voltammetry (CSV). It was found that while the concentrations of TdFe ranged from 27.8 to 82.0 nM, DrFe concentrations changed in a much narrower range from 6.8 to 13.3 nM. The annual mean concentrations of DrFe also ranged from 7.1 to 12.6 nM at the 12 sites monitored over the 4 years of the study (2017–2020). Considering the obvious changes in temperature (T), chlorophyll a (Chl a) concentrations (Chl a contents were higher in May, July and September than in March and November), and nutrients over a year in this zone, the consumption of DrFe was expected; the supplement of DrFe observed may have resulted from the transformation of strong organically complexed iron by photoreduction and cell surface reduction. Additionally, a pre-liminary conclusion was drawn based on the theoretical calculation of Fe* that the concentration of DrFe was sufficient to meet the phytoplankton demand.

An assessment of statistical interpolation methods suited for gridded rainfall datasets - Yuexiao Liu; Lu Zhuo; Maria Pregnolato; Dawei Han (International Journal of Climatology, 2022)
Accurate spatial distribution information of rainfall is essential to rainfall‐induced hazard predictions and statistical interpolation methods may serve as a useful tool to produce a detailed distribution from coarse data sources. Although numerous comparison studies about different interpolation methods have been conducted on irregular rain‐gauge networks, there is a need to perform such work on the increasingly available gridded rainfall data. Carried out in the Emilia‐Romagna region (Italy) from 2008 to 2018, this study aims to examine accurate and appropriate interpolation methods to produce finer rainfall surface maps based on the 0.25° × 0.25° ERA5 gridded precipitation datasets. Five interpolation techniques, namely Thiessen polygons, Inverse Distance Weighting (IDW), Thin Plate Spline (TPS), Ordinary Kriging (OK) and ordinary Co‐Kriging (CoK), have been selected and compared at different time scales (annual, monthly and annual maximum daily precipitation). To assess the accuracy, the leave‐one‐out‐cross‐validation test was used by using the indexes of Bias, correlation coefficient, the Nash‐Sutcliffe Efficiency, Root Mean Square Error and the Kling‐Gupta Efficiency (KGE). Additionally, visual inspections are employed to evaluate the plausibility of the interpolated maps. Results show: (a) All five interpolation methods have certain capabilities to improve spatial resolution, but they fail on accuracy at the daily scale. The OK generally outperforms the other four methods, while TPS shows better performance through the visual inspection at the monthly scale; (b) Unlike in the case of the interpolation using conventional point‐based rain‐gauge data, the multivariate method CoK is inferior to the univariate ones and the p ‐power of the IDW also differs and (c) Winter and spring results are better than those of summer and autumn. This study has provided useful guidance on choosing suitable rainfall interpolation methods for gridded datasets, which can be expanded in other regions and data sources to explore the generality of the conclusions.

Circ_PRKDC knockdown promotes skin wound healing by enhancing keratinocyte migration via miR-31/FBN1 axis - Dawei Han; Wenhui Liu; Guangshuai Li; Linbo Liu (Journal of Molecular Histology, 2021)

Paleoclimatic proxies from global closed basins and the possible beginning of Anthropocene - Yu Li; Qin Han; Lu Hao; Xinzhong Zhang; Dawei Chen; Yuxin Zhang; Lingmei Xu; Wangting Ye; Simin Peng; Yichan Li; Zhuowen Feng; Hebin Liu (Journal of Geographical Sciences, 2021)

Heavy metals in sediments of Yellow Sea and East China Sea: Chemical speciation, distribution, influence factor, and contamination - Miao Zhao; Shenghui Zhang; Haitao Han; Dawei Pan (Journal of Oceanology and Limnology, 2021)

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Species, Spatial-Temporal Distribution, and Contamination Assessment of Trace Metals in Typical Mariculture Area of North China - Dawei Pan; Xiaoyan Ding; Haitao Han; Shenghui Zhang; Chenchen Wang (Frontiers in Marine Science, 2020)

Metabolite profiling of Huaiyang Medicago polymorpha with different mowing crops - Na Guo; Dawei Yang; Changxi Liu; Han Yan; Xiaofang Yang; Xiaoqin Wang; Bin Fan (Natural Product Research, 2020)

Stripping Voltammetric Determination of Lead in Coastal Waters With a Functional Micro-Needle Electrode - Haitao Han; Dawei Pan; Ying Li; Jie Wang; Chenchen Wang (Frontiers in Marine Science, 2020)

Application of hydrological model simulations in landslide predictions - Binru Zhao; Qiang Dai; Dawei Han; Jun Zhang; Lu Zhuo; Matteo Berti (Landslides, 2020)

Isorhynchophylline enhances Nrf2 and inhibits MAPK pathway in cardiac hypertrophy - Yongtao Zhang; Yuqian Cui; Shuai Dai; Wei Deng; Hao Wang; Weidong Qin; Hongna Yang; Han Liu; Jinfeng Yue; Dawei Wu; Jing Wang; Haipeng Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Estimation of soil moisture using modified antecedent precipitation index with application in landslide predictions - Binru Zhao; Qiang Dai; Dawei Han; Huichao Dai; Jingqiao Mao; Lu Zhuo; Guiwen Rong (Landslides, 2019)

Spatio‐temporal drought patterns of multiple drought indices based on precipitation and soil moisture: A case study in South Korea - Moonhyuk Kwon; Hyun‐Han Kwon; Dawei Han (International Journal of Climatology, 2019)
This study aims to explore the spatio‐temporal characteristics of meteorological and agricultural droughts using the standardized precipitation index (SPI) and standardized soil moisture index (SSI), respectively, as well as their relationships over the past three decades (1986–2016) in South Korea. The SSI shows less frequent droughts and longer drought duration compared to the SPI, due to the gradual decrease in the autocorrelation functions of the SSI. The strongest cross‐correlations are observed at a 1‐month lag between the SPI and SSI for most stations. Thus, the SPI could be more appropriate for defining the onset of a drought, whereas the SSI appears to be more effective for describing drought persistence. Moreover, the transition from meteorological to agricultural droughts is significantly dependent on the season, indicating that the transition between them is highly correlated with antecedent moisture conditions. The copula‐based multivariate standardized drought index (MSDI) is introduced to explicitly postulate interdependence between the SPI and SSI in the context of a multivariate probability distribution. We employ a hierarchical agglomerative clustering approach along with a quantile regression model to better understand the spatio‐temporal pattern of the MSDI. More drought episodes under moderate to severe drought conditions are observed along the southern coast of South Korea. Additionally, persistent droughts with higher severity are observed in the northern part of South Korea, which may be attributed to a significant decreasing trend (or increasing drought risk).

Biochar promotes methane production at high acetate concentrations in anaerobic soils - Leilei Xiao; Fanghua Liu; Hengduo Xu; Dawei Feng; Jinchao Liu; Guangxuan Han (Environmental Chemistry Letters, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

A structural and data-driven approach to engineering a plant cytochrome P450 enzyme - Dawei Li; Yongshuo Ma; Yuan Zhou; Junbo Gou; Yang Zhong; Lingling Zhao; Lida Han; Sergey Ovchinnikov; Ling Ma; Sanwen Huang; Per Greisen; Yi Shang (Science China Life Sciences, 2019)

Anodic stripping voltammetric analysis of different species of copper in seawater using an electrochemical sensor - Xueping Hu; Dawei Pan; Haitao Han; Chenchen Wang (Journal of Oceanography, 2019)

Exploration of the creep properties of undisturbed shear zone soil of the Huangtupo landslide - Chun Li; Huiming Tang; Dawei Han; Zongxing Zou (Bulletin of Engineering Geology and the Environment, 2019)

Simultaneous Speciation Analysis of Trace Heavy Metals (Cu, Pb, Cd and Zn) in Seawater from Sishili Bay, North Yellow Sea, China - Haitao Han; Dawei Pan; Shenghui Zhang; Chenchen Wang; Xueping Hu; Yongcong Wang; Fei Pan (Bulletin of Environmental Contamination and Toxicology, 2018)

Biophysical heterogeneity in the tympanic membrane of the Asian water monitor lizard, Varanus salvator - Dawei Han; Bruce A. Young (Zoomorphology, 2018)

Vertical profile, contamination assessment of mercury and arsenic in sediment cores from typical intertidal zones of China - Chenchen Wang; Dawei Pan; Haitao Han; Xueping Hu (Environmental Monitoring and Assessment, 2018)

Transcriptome profile analysis reveals cardiotoxicity of maduramicin in primary chicken myocardial cells - Xiuge Gao; Lin Peng; Xiangchun Ruan; Xin Chen; Hui Ji; Junxiao Ma; Han Ni; Shanxiang Jiang; Dawei Guo (Archives of Toxicology, 2018)

Assessment of flood inundation mapping of Surat city by coupled 1D/2D hydrodynamic modeling: a case application of the new HEC-RAS 5 - Dhruvesh P. Patel; Jorge A. Ramirez; Prashant K. Srivastava; Michaela Bray; Dawei Han (Natural Hazards, 2017)

Exploration of empirical relationship between surface soil temperature and surface soil moisture over two catchments of contrasting climates and land covers - Lu Zhuo; Dawei Han; Qiang Dai (Arabian Journal of Geosciences, 2017)

Identification and validation of major QTLs and epistatic interactions for seed oil content in soybeans under multiple environments based on a high-density map - Qi Zhaoming; Zhang Xiaoying; Qi Huidong; Xin Dawei; Han Xue; Jiang Hongwei; Yin Zhengong; Zhang Zhanguo; Zhang Jinzhu; Zhu Rongsheng; Hu Zhenbang; Liu Chunyan; et al. (Euphytica, 2017)

Study on the Hydrolysis Kinetics of Dimethyl Disulfide - Dawei Han; Dongdong Yan; Aocheng Cao; Wensheng Fang; Xianli Wang; Zhaoxin Song; Yuan Li; Canbin Ouyang; Meixia Guo; Qiuxia Wang (Water, Air, & Soil Pollution, 2017)

The role of apparent diffusion coefficient values in characterization of solid focal liver lesions: a prospective and comparative clinical study - Dawei Yang; Jie Zhang; Dan Han; Erhu Jin; Zhenghan Yang (Science China Life Sciences, 2017)

Calculation method and application of loss of life caused by dam break in China - Dongjing Huang; Zhongbo Yu; Yiping Li; Dawei Han; Lili Zhao; Qi Chu (Natural Hazards, 2017)

Integrating Soil Hydraulic Parameter and Microwave Precipitation with Morphometric Analysis for Watershed Prioritization - Swati Maurya; Prashant K. Srivastava; Manika Gupta; Tanvir Islam; Dawei Han (Water Resources Management, 2016)

The Effects of Biochar Amendment on Dimethyl Disulfide Emission and Efficacy Against Soil-Borne Pests - Qiuxia Wang; Wensheng Fang; Dongdong Yan; Dawei Han; Yuan Li; Canbin Ouyang; Meixia Guo; Aocheng Cao (Water, Air, & Soil Pollution, 2016)

Seasonal evaluation of evapotranspiration fluxes from MODIS satellite and mesoscale model downscaled global reanalysis datasets - Prashant K. Srivastava; Dawei Han; Tanvir Islam; George P. Petropoulos; Manika Gupta; Qiang Dai (Theoretical and Applied Climatology, 2016)

Exploration of optimal time steps for daily precipitation bias correction: a case study using a single grid of RCM on the River Exe in southwest England - Kue Bum Kim; Michaela Bray; Dawei Han (Hydrological Sciences Journal, 2016)

Seasonal ensemble generator for radar rainfall using copula and autoregressive model - Qiang Dai; Dawei Han; Lu Zhuo; Jun Zhang; Tanvir Islam; Prashant K. Srivastava (Stochastic Environmental Research and Risk Assessment, 2016)

Cathodic stripping voltammetric determination of chromium in coastal waters on cubic Nano-titanium carbide loaded gold nanoparticles modified electrode - Haitao Han; Dawei Pan; Dongyan Liu; Xueping Hu; Mingyue Lin; Fei Li (Frontiers in Marine Science, 2015)

Appraisal of NLDAS-2 Multi-Model Simulated Soil Moistures for Hydrological Modelling - Lu Zhuo; Dawei Han; Qiang Dai; Tanvir Islam; Prashant K. Srivastava (Water Resources Management, 2015)

A real-time flood forecasting system with dual updating of the NWP rainfall and the river flow - Jia Liu; Jianhua Wang; Shibing Pan; Kewang Tang; Chuanzhe Li; Dawei Han (Natural Hazards, 2015)

Predicting streamflows to a multipurpose reservoir using artificial neural networks and regression techniques - Muhammad Hassan; Muhammad Ali Shamim; Hashim Nisar Hashmi; Syed Zishan Ashiq; Imtiaz Ahmed; Ghufran Ahmed Pasha; Usman Ali Naeem; Abdul Razzaq Ghumman; Dawei Han (Earth Science Informatics, 2015)

Modeling groundwater quality over a humid subtropical region using numerical indices, earth observation datasets, and X-ray diffraction technique: a case study of Allahabad district, India - Sudhir Kumar Singh; Prashant K. Srivastava; Dharmveer Singh; Dawei Han; Sandeep Kumar Gautam; A. C. Pandey (Environmental Geochemistry and Health, 2015)

Modelling radar-rainfall estimation uncertainties using elliptical and Archimedean copulas with different marginal distributions - Qiang Dai; Dawei Han; Miguel A. Rico-Ramirez; Tanvir Islam (Hydrological Sciences Journal, 2014)

Meta-analysis of influential factors on crop yield estimation by remote sensing - Jing Huang; Dawei Han (International Journal of Remote Sensing, 2014)

Association of the HTR2A gene with alcohol and heroin abuse - Jian Cao; Xiangtao Liu; Shizhong Han; Clarence K. Zhang; Zongzhi Liu; Dawei Li (Human Genetics, 2014)

Erratum to: Identification of QTLs for seed and pod traits in soybean and analysis for additive effects and epistatic effects of QTLs among multiple environments - Zhe Yang; Dawei Xin; Chunyan Liu; Hongwei Jiang; Xue Han; Yanan Sun; Zhaoming Qi; Guohua Hu; Qingshan Chen (Molecular Genetics and Genomics, 2013)

Identification of QTLs for seed and pod traits in soybean and analysis for additive effects and epistatic effects of QTLs among multiple environments - Zhe Yang; Dawei Xin; Chunyan Liu; Hongwei Jiang; Xue Han; Yanan Sun; Zhaoming Qi; Guohua Hu; Qingshan Chen (Molecular Genetics and Genomics, 2013)

The impact of raindrop drift in a three-dimensional wind field on a radar–gauge rainfall comparison - Qiang Dai; Dawei Han; Miguel A. Rico-Ramirez; Tanvir Islam (International Journal of Remote Sensing, 2013)

Data Fusion Techniques for Improving Soil Moisture Deficit Using SMOS Satellite and WRF-NOAH Land Surface Model - Prashant K. Srivastava; Dawei Han; Miguel A. Rico-Ramirez; Deleen Al-Shrafany; Tanvir Islam (Water Resources Management, 2013)

Machine Learning Techniques for Downscaling SMOS Satellite Soil Moisture Using MODIS Land Surface Temperature for Hydrological Application - Prashant K. Srivastava; Dawei Han; Miguel Rico Ramirez; Tanvir Islam (Water Resources Management, 2013)

Fuzzy logic based melting layer recognition from 3 GHz dual polarization radar: appraisal with NWP model and radio sounding observations - Tanvir Islam; Miguel A. Rico-Ramirez; Dawei Han; Michaela Bray; Prashant K. Srivastava (Theoretical and Applied Climatology, 2013)

Error Correction Modelling of Wind Speed Through Hydro-Meteorological Parameters and Mesoscale Model: A Hybrid Approach - Asnor Muizan Ishak; Renji Remesan; Prashant K. Srivastava; Tanvir Islam; Dawei Han (Water Resources Management, 2013)

Integrated framework for monitoring groundwater pollution using a geographical information system and multivariate analysis - Prashant K. Srivastava; Dawei Han; Manika Gupta; Saumitra Mukherjee (Hydrological Sciences Journal, 2012)

Phylogenetic analysis of Beet necrotic yellow vein virus isolates from China - Min Li; Tao Liu; Bin Wang; Chenggui Han; Dawei Li; Jialin Yu (Virus Genes, 2008)

Complete nucleotide sequence of a new strain of Tobacco necrosis virus A infecting soybean in China and infectivity of its full-length cDNA clone - Dehui Xi; Jiang Li; Chenggui Han; Dawei Li; Jialin Yu; Xueping Zhou (Virus Genes, 2008)

Molecular characterization of two Chinese isolates of Beet mosaic virus - Haiying Xiang; Yan-Hong Han; Chenggui Han; Dawei Li; Jialin Yu (Virus Genes, 2007)